the first person forgot the +7, the answer is x=9/2
2007-01-03 08:49:40
·
answer #1
·
answered by Illiara 2
·
2⤊
0⤋
x - 4(x - 3) + 7 = 6 - (x - 4)
The first step would be to remove the parentheses by distributing the number outside. In the first set of parentheses, the -4 is being distributed; in the second set, just the minus sign (which is in actuality -1).
x - 4x + 12 + 7 = 6 - x + 4
Now, group like terms,
-3x + 19 = 2 - x
Move all x terms to the left hand side, all numbers to the right hand side,
-3x + x = 2 - 19
Now, group like terms again,
-2x = -17
Divide both sides by -2,
x = 17/2
2007-01-03 16:51:40
·
answer #2
·
answered by Puggy 7
·
1⤊
0⤋
Solving for x:
x-4(x-3)+7 = 6-(x-4)
x-4x+12+7 = 6-x+4
-3x+19 = -x +10
2x = 9
x = 4.5
2007-01-03 16:49:51
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
x-4x+12+7=6-x+4
-3x+19=10-x
+x +x
-2x+19=10
-19 -19
-2x=-9
x= -9/-2
x=4.5
2007-01-03 16:53:08
·
answer #4
·
answered by Noodle 2
·
1⤊
0⤋
x - 4x + 12 = 6 -x + 4
+x
2x -4x +12 = 6+4
-2x +12 = 10
-12
-2x = -2
/-2
x=1
2007-01-03 16:53:17
·
answer #5
·
answered by Katie B 1
·
1⤊
0⤋
x^2 - 4x - 3x +12 +7 = 10 - x
x^2 - 7x +19 = 10 - x
x^2 - 6x + 9
(x - 3)(x-3)
2007-01-03 16:56:58
·
answer #6
·
answered by Donny Dutch 4
·
0⤊
0⤋
x-4(x-3)+7=6-(x-4)
x-4x+12+7=6-x+4
-3x+19=10-x
9=2x
4.5=x
2007-01-03 16:51:22
·
answer #7
·
answered by CM 2
·
1⤊
0⤋
x-4x+12+7=6-x+4
x+x-4x=6+4-12-7
-2x=-9
x=9/2
x=4.5
2007-01-03 16:50:54
·
answer #8
·
answered by noni 2
·
1⤊
0⤋
x = 9/2 =4.5
2007-01-03 16:49:31
·
answer #9
·
answered by bagoftwix 3
·
0⤊
0⤋
x= -1/3(-9-x)? I might have expanded it wrong though
2007-01-03 16:52:48
·
answer #10
·
answered by what 2
·
0⤊
0⤋